On the New Weight Parameter of the Mixture Pareto Distribution and Its Application to Real Data - Chananet, Chanaphun; Phaphan, Wikanda (Applied Science and Engineering Progress, 2021)
This research aims to investigate the theoretical properties of new distribution which are based on the preceding well-known distributions by adding the new weight parameter. The new distribution is called the new weight parameter of the mixture of Pareto distribution. The advantage of the new distribution is the right-skewed distribution that is depending on the shape parameter. This property made the new mixture of Pareto distribution have high benefits of reliability engineering and survival analysis. Besides, we applied the purposed distribution to three sets of actual data: cement industry data, hard drive failure data, and heart attack data to show that new mixture Pareto distribution is fit to real data for generating data models.